Spinal anesthesia versus general anesthesia for percutaneous nephrolithotomy surgeries - a prospective study - Eddula, Mahesh; Patil, Vasant P. (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Percutaneous nephrolithotomy (PCNL) is a minimally invasive surgery for extracting renal and urinary stones, and a choice modality in large, multiple, and stag-horn stones. Anaesthesia for PCNL can be general or regional. Despite good results of PNCL with general anaesthesia, it may cause atelectasis, drug reactions, nausea, and vomiting. General anaesthesia (GA) has its limitations in the form of poor postoperative pain control, greater incidence of nausea and vomiting, prolonged recovery stays and prolonged hospitalizations. Methods: The study was performed in a tertiary care centre. A prospective, randomised study including 60 patients divided into 2 groups. Data collection tools included study proforma, numerical rating scale (NRS) scores and visual analog scale (VAS) scores. Data analysed using science and statistical packaged (SPSS) version 21, independent t tests and z-test for proportion. Results: The demographic data when statistically analysed showed no statistically significant differences between the groups. Haemoglobin percentage (Hb%) was significantly lower in GA group. Spinal anaesthesia (SA) group showed lower VAS and NRS scores hence lower requirement of pain relief and antiemetics. The post-operative complications were insignificant. Conclusions: We concluded that SA is safe and effective method as an alternative method for PCNL surgeries.